Mengapa Crafting Gagal? Workplace Belongingness sebagai Mata Rantai yang Hilang dalam Kesejahteraan Gen Z dan Milenial - Damayanti, Bella Febriana; Samian (Universitas Airlangga, 2025)
This study aims to examine the mediating role of workplace belongingness upon the effect of job crafting and leisure crafting on employee well-being based on Self-determination Theory (SDT). The research employed a cross-sectional survey method using data from Gen Z and Millennial employees (N=121) working in hybrid settings in Indonesia. The analysis was conducted using a Generalised Linear Model (GLM) Mediation approach. The findings revealed that: (1) The direct effect of both job crafting and leisure crafting on employee well-being are not statistically significant, and (2) workplace belongingness fully mediates the effect of job crafting and leisure crafting on employee well-being. These results suggest that job and leisure crafting alone may be insufficient to improve employee well-being unless such efforts foster a strong sense of connection to the organization or company, as well as when employees feel integrated, appreciated, and valued within their work community.